Socialization of the Love-Based Curriculum in the Teachers Working Group and the Principals Working Group of Islamic Elementary Schools in Plupuh Sub-district - Eko Rochmawan, Alfian; Hidayatul Amiin, Lailla; Hidayah, Nur (LPPM STAIMAS WONOGIRI, 2025)
Islamic education curriculum ideally emphasizes not only cognitive development but also the cultivation of affective and spiritual dimensions in learners. This community service program aims to socialize the concept of the Love-Based Curriculum as a new paradigm for strengthening character and spirituality within Madrasah Ibtidaiyah (Islamic elementary schools). The activity was conducted through the Teachers Working Group (Kelompok Kerja Guru or KKG) and the Principals Working Group (Kelompok Kerja Kepala Madrasah or KKM) in Plupuh Sub-district, Sragen Regency, involving 114 teachers and school principals. The program employed interactive lectures, reflective discussions, and practical sessions in designing lesson plans that integrate the values of compassion, empathy, and respect for diversity. The participatory approach enabled teachers to actively engage in understanding, contextualizing, and adapting the Love-Based Curriculum to their respective madrasah environments. The results revealed a significant increase in participants’ understanding of the importance of love-centered values in education and their growing awareness to transform classroom practices toward more humanistic and spiritual approaches. Participants agreed that the Love-Based Curriculum aligns with the vision of Islamic education as rahmatan lil ‘alamin (a mercy to all creation) and serves as a relevant response to the crisis of character and dehumanization in modern education. Therefore, this socialization program represents a strategic initial step toward developing a compassionate, empathetic, and exemplary culture within Islamic schools, paving the way for a more practical implementation of the Love-Based Curriculum in the future. Keywords: love-based curriculum, Islamic education, character, spirituality, teachers’ working group, principals’ working group.